A preliminary study of the effects of REM sleep deprivation on oxidative stress markers and vascular endothelium in animal model - Amin, Anis Ayuni (Universiti Sains Malaysia, 2015)
Oxidative stress is one of the factors involved in the development of endothelial dysfunction. Endothelial dysfunction is known to precede cardiovascular diseases; however the pathogenesis is poorly understood. Insufficient sleep has been shown to be associated with cardiovascular disease. The main aims of this study are to assess the serum levels of oxidative stress markers and to assess the morphological changes in vascular endothelium following REM sleep deprivation. Twenty four (24) male Sprague-Dawley rats were divided equally into three groups: free-moving control rats (FMC), 72-h REM sleep-deprived rats (REMsd) and tank control rats (TC). The rats were deprived from REM sleep using inverted flowerpot technique. Serum levels of oxidative stress markers, superoxide dismutase (SOD) and malondialdehyde (MDA) were measured using ELISA kits. Thoracic descending aortas were examined under the scanning electron microscope (SEM). The sleep deprived rats showed a significant reduction in body weight compared to controls despite no significant changes in the food consumption between the groups. There were no significant differences in the levels of SOD and MDA between the groups. The endothelium of REMsd group demonstrated a rough surface, dilatation of intercellular clefts and derangement of endothelial cells. There were also numerous fibrin networks with rich interlacing and trapped red blood cells. The endothelium appeared smooth with regular arrangement of the endothelial cells in FMC and TC groups. The present study suggests that REM sleep deprivation induced endothelial dysfunction that demonstrated by its structural damage. The endothelial damage might activate coagulation factors with subsequent fibrin formation. Excessive generation of fibrin leads to thrombosis and this study suggests that sleep disturbance is a potential risk factor in development of cardiovascular diseases. As there were no significant changes in the SOD and MDA, further studies are needed to identify other oxidative stress markers or other factors that might induce endothelial dysfunction.